PS10:185 Nodular localised cutaneous amyloidosis in a patient with systemic lupus erythematosus. (21st March 2018) - Deac Badarinza, M; Rednic, S; Pamfil, C; Baican, C; vasilache, A; Filipescu, I; Muresan, I; Balint, D; Damian, L
Abstract : Introduction: Nodular localised amyloidosis is a rare subtype of cutaneous amyloidosis, associated with various connective tissue diseases, mostly Sjogren's syndrome. Progression to systemic amyloidosis was described in 7%–50% cases. Amyloid deposition was also noted in hypertrofic lupus lesions. Purpose: To report a case of systemic lupus erythematosus (SLE) presenting with nodular localised cutaneous amyloidosis, followed up for 17 years. Methods: A 55 year patient was addressed to our tertiary unit with pain and swollen in both hands and multiple soft nodular lesions pink to brown on the chest and back. Results: Clinical examination and further investigations revealed inflammatory hand arthritis and polyserositis including pericarditis and pleural effusion. Laboratory showed antinuclear antibodies with low anti-dsDNA titer, positive anti-Ro antibodies, positive rheumatoid factor, C3 and C4 consumption. She had negative anti -cyclic citrullinated peptide antibodies and anti-LA antibodies, no sicca symptoms and no ultrasound modification of the salivary glands. The skin histopathology with Congo red staining revealed amyloid deposition in the dermis. A screening for multiple myeloma, including bone marrow biopsy, was negative. She was treated with hydroxychloroquine, and over the time with methotrexate, azathioprine (with loss of tolerance), acitretin (with no significant skin improvement), and topical glucocorticorticoids. New lesions appeared mostly upon cessation of SLE therapy, on traumatised areas and sun exposure, but were quite stable during sustained systemic therapy, suggesting some relation to disease activity. She developed new-onset cryoglobulinemia with increasing anti- Ro titers and rheumatoid factor, but has still normal immunoglobulins, complement fractions and LDH and no light chains on immunelectrophoresis. Conclusions: Nodular localised amyloidosis is rare in SLE. The lesions evolve slowly, are minimally influenced by systemic therapy, but a close monitoring for systemic amyloidosis or plasma cell dyscrasia is required even in longstanding cases.